In silico prediction of antigenic epitopes for the production of a human visceral leishmaniasis vaccine - Macedo Junior, Lafayete Modesto de (2019)
Through in silico analyzes we sought to identify and select Leishmania infantum epitopes potentially capable of triggering an immunogenic response to develop a commercial vaccine against human visceral leishmaniasis. Sequences were selected to obtain a specific database and subsequently, the genetic similarity with the complex of species causing Visceral Leishmaniasis (LV) was analyzed. Sequences of interest of L.infantum were selected. He then predicted secondary structure of the protein sequences and obtained B cell recognized epitopes along with his prediction of MHC class II epitope affinity. After this process, the tertiary protein structure was modeled for analysis of the generated protein model. It was observed by in silico analysis the desirable proteins and from their three-dimensional structures it was possible to arrive at the prediction of conformational epitopes. It is also noteworthy that the reliability of these results require experiments on benches.Through in silico analyzes, we sought to identify and select Leishmania infantum epitopes potentially capable of triggering an immunogenic response to develop a commercial vaccine against human visceral leishmaniasis. Sequences were selected to obtain a specific database and, afterwards, the genetic similarity with a complex of species causing Visceral Leishmaniasis (LV) was analyzed. Sequences of interest of L. infantum were selected. Secondary structure prediction of protein sequences and B cell recognized epitopes were predicted along with their prediction of MHC class II epitope affinity. After this process, the tertiary protein structure modeling was performed to analyze the generated protein model. By in silico analysis, the desirable proteins were observed, and from their three-dimensional structures, it was possible to predict the conformational epitopes. It is also noteworthy that the reliability of these results require experiments on benches.